Analisis Dana Berputar Pada Produk Pembiyaaan Bank Syariah Mandiri Cabang Jambi Ditinjau dari UU 21 Tahun 2008 - Rofiqoh Ferawati (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2019)
This study aims to reveal the analysis of revolving fund financing at Bank Syariah Mandiri Jambi Branch. This study uses a qualitative approach with data collection methods through observation, interviews, and documentation. Based on the research conducted, the following results and conclusions were obtained: (1) The analysis of revolving fund financing at Bank Syariah Mandiri Jambi Branch in 2015-2017 was carried out in accordance with the Islamic banking Law Number 21 of 2008 in carrying out any operational activities and transactions must be in accordance with Sharia principles, including filing, investigation, and analysis stages consisting of basic information, capability, capital, guarantees, and business conditions (2) Efforts made by Bank Mandiri Syariah Jambi Branch to mitigate revolving fund financing are selective in sorting customers, utilization of facility funds and monitoring through financial reports.